The Nature of Certainty in Ritual - Michaela Vlčková (Acta Universitatis Carolinae Theologica, 2020)
Liturgy is a privileged type of action: it is the actualisation of the Easter mystery, God’s salvation of His people, and the thanksgiving and praise of the Christian community. At the same time, liturgy must be seen as human behaviour and very specific – ritual behaviour. This study focuses on the concept of liturgy as a ritual which allows the exploration of the anthropological, physical, and performative part of liturgical action. This article demonstrates the basic elements in which the nature of this certainty is based in ritual (certainty based on the body, on traditionalism, on the form and on the doctrine).